Farnesiferol B and Kamolonol Isolated from Ferula assa-foetida are Potent BACE1 Inhibitors with Neuroprotective Effects - Oh, Jong Min; Shin, Woong-Hee; Kim, Bomi; Kim, Eonmi; Son, Hyun Ju; Kim, Hoon (Planta Medica, 2025)
Five compounds were isolated from Ferula assa-foetida and their beta-secretase 1 inhibitory activities were evaluated. Farnesiferol B and kamolonol showed potent beta-secretase 1 inhibitory activity with IC50 values of 8.11 and 1.00 µM and competitive inhibition patterns against beta-secretase 1 with Ki values of 6.51 and 0.41 µM, respectively. In silico pharmacokinetics showed that farnesiferol B was predicted to have high gastrointestinal absorption and blood-brain barrier permeability. In cell studies, farnesiferol B and kamolonol were nontoxic to normal Madin-Darby canine kidney and neuroblastoma cells, and both showed protective effects on neuroblastoma cells for Aβ42-induced neurotoxicity. In molecular docking simulations, we found that the efficacy of the compounds may be related to their interaction with the flap region and hydrogen bonding with ARG368. In addition, molecular dynamics simulation of kamolonol showed the ligand maintained its stability in interaction with the loop residues. These results show that farnesiferol B and kamolonol are potent beta-secretase 1 inhibitors with neuroprotective effects, suggesting that they are potential candidates for the treatment of neurodegenerative disorders, such as Alzheimerʼs disease.
Keywords: Apiaceae; Ferula assa-foetida; farnesiferol B; kamolonol; potent beta-secretase 1 inhibitory activity; kinetics; docking simulation; molecular dynamics; cell study